UV exposure modulates hemidesmosome plasticity, contributing to long‐term pigmentation in human skin. Issue 1 (17th February 2015) - Coelho, Sergio G; Valencia, Julio C; Yin, Lanlan; Smuda, Christoph; Mahns, Andre; Kolbe, Ludger; Miller, Sharon A; Beer, Janusz Z; Zhang, Guofeng; Tuma, Pamela L; Hearing, Vincent J
Abstract Human skin colour, ie pigmentation, differs widely among individuals, as do their responses to various types of ultraviolet radiation (UV) and their risks of skin cancer. In some individuals, UV‐induced pigmentation persists for months to years in a phenomenon termed long‐lasting pigmentation (LLP). It is unclear whether LLP is an indicator of potential risk for skin cancer. LLP seems to have similar features to other forms of hyperpigmentation, eg solar lentigines or age spots, which are clinical markers of photodamage and risk factors for precancerous lesions. To investigate what UV‐induced molecular changes may persist in individuals with LLP, clinical specimens from non‐sunburn‐inducing repeated UV exposures (UVA, UVB or UVA + UVB) at 4 months post‐exposure (short‐term LLP) were evaluated by microarray analysis and dataset mining. Validated targets were further evaluated in clinical specimens from six healthy individuals (three LLP+ and three LLP−) followed for more than 9 months (long‐term LLP) who initially received a single sunburn‐inducing UVA + UVB exposure. The results support a UV‐induced hyperpigmentation model in which basal keratinocytes have an impaired ability to remove melanin that leads to a compensatory mechanism by neighbouring keratinocytes with increased proliferative capacity to maintain skin homeostasis. The attenuated expression of SOX7 and other hemidesmosomal components (integrin α6β4 and plectin) leads to increased melanosome uptake by keratinocytes and points to a spatial regulation within the epidermis. The reduced density of hemidesmosomes provides supporting evidence for plasticity at the epidermal–dermal junction. Altered hemidesmosome plasticity, and the sustained nature of LLP, may be mediated by the role of SOX7 in basal keratinocytes. The long‐term sustained subtle changes detected are modest, but sufficient to create dramatic visual differences in skin colour. These results suggest that the hyperpigmentation phenomenon leading to increased interdigitation develops in order to maintain normal skin homeostasis in individuals with LLP. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.